2019
DOI: 10.5811/westjem.2019.2.40979
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped Classroom: A Critical Appraisal

Abstract: Introduction The objective of this study was to review and critically appraise the medical education literature pertaining to a flipped-classroom (FC) education model, and to highlight influential papers that inform our current understanding of the role of the FC in medical education. Methods A search of the English-language literature querying Education Resources Information Center (ERIC), PsychINFO, PubMed, and Scopus identified 296 papers related to the FC using eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 22 publications
2
27
0
4
Order By: Relevance
“…These active-learning approaches are gaining more and more popularity in medical education. While the efficacy of FC over LBT seems to rest on subjects and specific settings [ 30 ]. In the present study, we implemented FC with CBL combined in the class activities in nephrology clerkship students and compared the students’ perspectives and performance with those experienced LBT teaching modality, which was a novel attempt and provided insights for teaching of other modules in nephrology.…”
Section: Discussionmentioning
confidence: 99%
“…These active-learning approaches are gaining more and more popularity in medical education. While the efficacy of FC over LBT seems to rest on subjects and specific settings [ 30 ]. In the present study, we implemented FC with CBL combined in the class activities in nephrology clerkship students and compared the students’ perspectives and performance with those experienced LBT teaching modality, which was a novel attempt and provided insights for teaching of other modules in nephrology.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of an emergency medicine clerkship for fourth-year medical students, over a third did not use asynchronous resources at all during the clerkship, though nearly 70% stated they preferred that modality ( 14 ). Furthermore, faculty time requirements may be prohibitive; a critical appraisal of recent flipped classroom literature suggested that creating high-quality asynchronous content can be more time and labor intensive for faculty than creating traditional didactics ( 15 ).…”
Section: Tips For Completely Asynchronous Learningmentioning
confidence: 99%
“…Even in situations in which some in-person teaching is necessary (e.g., teaching new learners a procedure in a simulation laboratory), asynchronous learning may help streamline or truncate in-person didactics. For instance, flipped classroom and blended learning approaches have good success when used for procedural teaching ( 15 ) and could minimize the time learners need to spend in a simulation center.…”
Section: Tips For Completely Asynchronous Learningmentioning
confidence: 99%
“…Many works studied the implementation of the FC method in a specific discipline such as economics [13], language study [14], and chemistry [15]. Meanwhile, some studies only focus on reviewing the FC implementation papers, such as [16] [17] [18] [19]. Most of these literature review papers studied the FC implementation's articles in various disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these literature review papers studied the FC implementation's articles in various disciplines. On the contrary, [18] only reviewed papers that discussed the implementation of FC in medical education. Unlike the other papers that analyzed the benefits and challenges of the FC implementation, [17] examined only the effect of FC on learning outcomes and student satisfaction.…”
Section: Introductionmentioning
confidence: 99%